1996
DOI: 10.1183/09031936.96.09040709
|View full text |Cite
|
Sign up to set email alerts
|

Airway structure and inflammatory cells in fatal attacks of asthma

Abstract: Fatal attacks of asthma usually occur against a background of chronic persistent symptoms, presumably due to chronic airway inflammation and changes in airway wall structure. Death from asthma is usually attributed to excessive airway narrowing due to a combination of muscle spasm and mucous plugging. To test the hypothesis that airway wall structure and/or the inflammatory cell profile are related to the duration of a fatal attack of asthma, inflammatory cell profiles and airway structure were examined in cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
129
1
12

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(146 citation statements)
references
References 36 publications
4
129
1
12
Order By: Relevance
“…It is possible that the increased numbers of eosinophils in the cases of fatal asthma is due to factors related not only to severity but also to a final episode of asthma. SUR et al [20] have shown that cell profiles in the airway wall may be temporally related to a fatal attack of asthma, and we have recently confirmed these findings [39]. In both studies, neutrophils were observed in much smaller numbers than lymphocytes and eosinophils in cases of fatal asthma, and may be important in the pathogenesis of a fatal attack of asthma.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is possible that the increased numbers of eosinophils in the cases of fatal asthma is due to factors related not only to severity but also to a final episode of asthma. SUR et al [20] have shown that cell profiles in the airway wall may be temporally related to a fatal attack of asthma, and we have recently confirmed these findings [39]. In both studies, neutrophils were observed in much smaller numbers than lymphocytes and eosinophils in cases of fatal asthma, and may be important in the pathogenesis of a fatal attack of asthma.…”
Section: Discussionsupporting
confidence: 76%
“…The relationship between airway inflammation and structural change is of interest in asthma. Longstanding asthma is related to fixed airway narrowing [41], and the rapidity of death from an attack of asthma is related not only to inflammatory cell profiles but also to the size of mucous glands [39]. It is assumed that chronic airway inflammation results in structural change.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic obstructive pulmonary disease this consists predominantly of lymphocytes and neutrophils [61] and in asthma predominantly of lymphocytes and eosinophils [34,62], although the relative numbers of neutrophils and eosinophils may vary in both conditions [62,63]. However, these inflammatory cells may be less important than mast cells in determining airway smooth muscle function.…”
Section: Relationship Of Airway Smooth Muscle and Airway Inflammationmentioning
confidence: 99%
“…These results suggest that changes in MUC gene expression, especially MUC5B, are associated with airway diseases. The source of increased mucus production in diseases such as asthma and COPD is due at least partially to an increased number of goblet cells in the airway epithelium (11)(12)(13). Studies have linked goblet cell metaplasia to the increase of mucin gene expression in airway epithelial cells (10,14).…”
mentioning
confidence: 99%
“…In the lung, synthesis and secretion of mucins are restricted largely to the airway with little to no expression in alveolar airspaces (1). Although at least eight mucin genes (MUC 1, 2, 4, 5AC, 5B, 7,8,13) have been found to be expressed in adult human lung (4), MUC5AC and MUC5B appear to be the predominant genes expressed, and their glycoprotein products are the most abundant in mucus secretions (4, 6 -9). MUC5AC appears to be produced mainly in the airway epithelium by goblet cells (8,10), while MUC5B is mostly produced in the underlying submucosal glands (10).…”
mentioning
confidence: 99%